Molecular studies of phages-Klebsiella pneumoniae in mucoid environment: innovative use of mucolytic agents prior to the administration of lytic phages - Pacios, Olga; Blasco, Lucía; Ortiz Cartagena, Concha; Bleriot, Inés; Fernández-García, Laura; López, María; Barrio-Pujante, Antonio; Cuenca, Felipe Fernández; Aracil, Belén; Oteo-Iglesias, Jesús; Tomás, María (Frontiers in Microbiology, 2023)
Mucins are important glycoproteins that form a protective layer throughout the gastrointestinal and respiratory tracts. There is scientific evidence of increase in phageresistance in the presence of mucin for some bacterial pathogens. Manipulation in mucin composition may ultimately influence the effectiveness of phage therapy. In this work, two clinical strains of K. pneumoniae (K3574 and K3325), were exposed to the lytic bacteriophage vB_KpnS-VAC35 in the presence and absence of mucin on a long-term co-evolution assay, in an attempt to mimic in vitro the exposure to mucins that bacteria and their phages face in vivo. Enumerations of the bacterial and phage counts at regular time intervals were conducted, and extraction of the genomic DNA of co-evolved bacteria to the phage, the mucin and both was performed. We determined the frequency of phage-resistant mutants in the presence and absence of mucin and including a mucolytic agent (N-acetyl L-cysteine, NAC), and sequenced them using Nanopore. We phenotypically demonstrated that the presence of mucin induces the emergence of bacterial resistance against lytic phages, effectively decreased in the presence of NAC. In addition, the genomic analysis revealed some of the genes relevant to the development of phage resistance in long-term co-evolution, with a special focus on the mucoid environment. Genes involved in the metabolism of carbohydrates were mutated in the presence of mucin. In conclusion, the use of mucolytic agents prior to the administration of lytic phages could be an interesting therapeutic option when addressing K. pneumoniae infections in environments where mucin is overproduced.